Gestión por procesos en el área administrativa del Gobierno Provincial de Los Ríos durante el periodo 2021. - Troya Badillo, Jean Carlos (2022)
Process management is a modern technique of business organization, which is used within any company, both public and private, in order that the activities carried out within the institution are carried out efficiently and effectively, and always meeting the objectives, The main characteristic of this business management tool is the focus on customers, or users, through teamwork, in addition to the fact that the processes that are carried out have an owner or person in charge of monitoring compliance with the objective of this. The case study "Management by Processes in the Administrative Area of the Provincial Government of Los Ríos during the period 2021", is carried out in the Provincial GAD of Los Ríos, with the aim of ensuring that the processes within the administrative management of the Provincial GAD of Los Ríos are carried out according to what their statutes indicate and the other laws that govern them. Research Financial, Administrative, Tax, Audit, Control Management, with its subline of Companies and Public and Private Institutions.